Case Report: Focal cryoablation vs. radiofrequency ablation in a pediatric patient with para-Hisian accessory pathway with effect from the non-coronary aortic cusp - Maksut, Zhandos; Zhanbolatkyzy, Raushan; Bakytzhanuly, Abay; Bajgalkanova, Almira; Ergül, Yakup; Nuralinov, Omirbek (Frontiers in Pediatrics, 2024)
Twelve – lead electrocardiogram (ECG) of a pediatric patient with Wolff – Parkinson – White syndrome was consistent with the anteroseptal accessory pathway (AP). Patient had three ablation procedures due to the recurrences of the arrhythmia. In our case, successful cryoablation was performed in the non-coronary cusp of the aortic root.